The effectiveness and safety of traditional Chinese medicine for the treatment of children with COVID-19. Issue 30 (24th July 2020) - Li, Yanqing; Bi, Lin; Li, Yulin; Hu, Xiongxin; Wang, Quanxi; Liang, Xin; Yu, Xujun; Dong, Liang; Xie, Quan
Abstract: Introduction: With the widespread spread of novel coronavirus pneumonia, more and more countries have been affected. Some research reports have shown that traditional Chinese medicine has a significant effect on COVID-19 infection, and the treatment of traditional Chinese medicine is used in some special people, such as children. At present, there is a lack of high-quality systematic reviews on the safety and efficacy of using Chinese medicine to treat children with novel coronavirus pneumonia. Materials and methods: We will search Cochran library, MEDLINE, EMBASE, China National Knowledge Infrastructure Database (CNKI), China Biomedical Database (CBM), VIP Database (VIP), and Wanfang database for research. This study includes randomized controlled trials (RCTs) and non-RCTs, and uses the Cochrane systematic review to review the safety and efficacy of traditional Chinese medicine in preventing and treating children with novel coronavirus pneumonia. RCT research tools and quantitative research quality assessment tools for non-randomized studies will be used to assess the risk of bias in studies included in the systematic review. We will use Revman 5.3 software for meta-analysis, the main result is odds ratio, and then a subgroup analysis will be performed based on the age, intervention degree, and disease severity of the patients reviewed. Ethics and dissemination: This systematic review protocol is designed to provide evidence regarding the effectiveness and safety of traditional Chinese medicine for the treatment of children with COVID-19, such evidence may be useful and important for clinical treatment decisions. The results should be disseminated through publication in a peer-reviewed journal. Since the data and results used in the systematic review will be extracted exclusively from published studies, approval from an ethics committee will not be required. Registration information: PROSPERO CRD42020179150.